Money and Inflation: The Role of Persistent Velocity Movements - Makram El-Shagi; Sebastian Giesen (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
While the long run relation between money and inflation is well established, empirical evidence on the adjustment to the long run equilibrium is very heterogeneous. In the present paper we use a multivariate state space framework, that substantially expands the traditional vector error correction approach, to analyze the short run impact of money on prices. We contribute to the literature in three ways: First, we distinguish changes in velocity of money that are due to institutional developments and thus do not induce inflationary pressure, and changes that reflect transitory movements in money demand. This is achieved with a newly developed multivariate unobserved components decomposition. Second, we analyze whether the high volatility of the transmission from monetary pressure to inflation follows some structure, i.e., if the parameter regime can assumed to be constant. Finally, we use our model to illustrate the consequences of the monetary policy of the Fed that has been employed to mitigate the impact of the financial crisis, simulating different exit strategy scenarios. – – Während die Langfristbeziehung zwischen Geld und Inflation in der Literatur als weitgehend gesichert gilt, ist empirische Evidenz bezüglich der Anpassung an das Langfristgleichgewicht ambivalent. Im vorliegenden Papier verwenden wir ein multivariates Zustandsraummodell, das eine erhebliche Erweiterung des traditionell verwendeten Fehlerkorrekturrahmens darstellt, um die Konsequenzen von Geldmengenveränderungen für die Inflation zu analysieren. Wir tragen auf dreierlei Weise zur bestehenden Literatur bei: Erstens unterscheiden wir Veränderungen der Umlaufsgeschwindigkeit, die dauerhafter Natur sind - z.B. ausgelöst durch institutionelle Entwicklungen - von vorübergehenden Veränderungen. Zweitens überprüfen wir ausführlich, inwiefern die Beziehung zwischen Geldmenge und Inflation stabil ist, d.h. ob das Parameterregime als konstant unterstellt werden kann. Schließlich illustrieren wir auf der Grundlage unserer Schätzungen die Konsequenzen der jüngsten Geldpolitik der Federal Reserve, die eingesetzt wurde, um die Folgen der Finanzmarktkrise abzumildern, unter verschiedenen Annahmen bezüglich der Exit-Strategie.
urn:nbn:de:101:1-2010031934
Keywords: E31; E52; C32; 330; multivariate state space model; inflation; money; Umlaufsgeschwindigkeit; multivariates Zustandsraummodell; Inflation; Geldmenge; Geldumlaufgeschwindigkeit; Zustandsraummodell; Geldmenge; Inflation; Schätzung; Geldpolitik; Finanzmarktkrise; Reaktionsfunktion; USA